Tauhid-Based Student Management in Islamic Schools: A Case Study at SDIT Hidayatullah Yogyakarta - Ihsannudin , Arif; Syifana, Najwa; Mutiah, Nurul (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study explores the implementation of tauhid-based student management at SDIT Hidayatullah Yogyakarta, aiming to understand how Islamic spiritual values are embedded within the Integral Program Based on Tauhid (PIBT) and how they contribute to character formation and educational quality. This research addresses a growing need for value-oriented governance in Islamic schools, proposing a comprehensive model that merges religious values with contemporary educational practices. Design/methods – Employing a descriptive qualitative methodology and single-case study design, the research gathered data through semi-structured interviews, direct observation, and document analysis. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model involving data reduction, display, and conclusion drawing, supported by source triangulation and member checking to ensure validity. Findings – The study found that tauhid-based student management at SDIT Hidayatullah encompasses integrated systems in planning, admissions, grouping, attendance, discipline, evaluation, and character development. The PIBT framework enables the school to holistically instill tauhid values into academic and non-academic activities, leading to high student retention, strong character growth, and institutional trust. Research implications/limitations – As a context-specific case study, the findings may be limited in generalizability beyond similar Islamic school environments. The single-site focus and cultural specificity should be considered when applying the model to broader contexts. Practical implications – The results present a replicable model for Islamic educational institutions seeking to integrate spiritual identity into student governance systems. This research supports policy development, curriculum design, and institutional reform in Islamic education aimed at cultivating moral and academic excellence. Originality/value – This paper provides empirical evidence on how tauhid-based frameworks can be effectively operationalized in student management systems, offering new insights into the synergy between spiritual vision and educational leadership in Islamic primary schools.